PENGARUH MODEL KOOPERATIF TIPE VAK TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA SMA - Sumarni Susilawati (Jurnal Penalaran dan Riset Matematika, 2022)
Students' mathematical understanding ability at SMA Muhammadiyah Makassar is in the low category. This is based on the results of preliminary observations that researchers conducted at the school, students were unable to relate new material to previous material that had been learned. This is also indicated by the low test scores of class X students, namely with an average below the KKM score. An alternative is needed to choose the right learning model, one of which is the Visual Auditory Kinesthetic (VAK) learning model. The purpose of this study was to determine the effect of Visual Auditory Kinesthetic (VAK) type cooperative learning model on the ability to understand mathematical concepts of grade X students of SMA Muhammadiyah Makassar. The research approach used was a quantitative approach with the type of pre-experiment research and the research design was a one group pretest-posttest design. The research sample was determined using a random sampling technique (sample random sampling), namely not all populations were used as sample members. The population in this study were all students of class X SMA Muhammadiyah Makassar. The sample used in the study was social studies class students as many as 9 people. The research instrument is a questionnaire, pretest and posttest in which there are indicators of mathematical understanding. The tests used were in the form of descriptions. Research hypothesis testing using paired samples t-test on SPSS system. Based on the results of hypothesis testing with a significance level of